The past, present, and future of anti-idiotype antibodies - Murphy, William J.; Collins, Craig P.; Kohler, Heinz (Frontiers in Immunology, 2025)
Seminal discoveries led to the concept of the immune system as a complex network of antibodies and B-cells. In 1963, Kunkel et al. described individual antigenic specificities using antibodies directed against antibodies, hinting at the possibility of a network structure in the immune repertoire. In 1973, Jerne proposed the Network Theory that the immune system is a functional network of antibodies (idiotypes) and anti-idiotypic antibodies that are made in response due to the inherent immunogenicity of immunoglobulin variable chains. In 1974, anti-idiotypic responses were observed, providing proof of the Network Theory. In this review, the origin, as well as rise and fall, of idiotype research over the years is traced, citing examples of work that expanded the understanding of the network concept and its potential application. This includes broadly binding anti-idiotypic antibodies, anti-idiotype vaccines, anti-idiotypic antibodies as tools to trace monoclonal antibodies, and as immunotherapeutic biologicals. Future utility from using the Network Theory could involve cocktails of different monoclonal anti-idiotypic monoclonals. Studies can focus on how the Network Theory involves the generation of potential “antigen mirror” effects and how the network ultimately regulates both B and T cell responses over time. Despite the decline in popularity, aspects of the Network Theory are reemerging as evidence is generated on potential roles during host responses to pathogens or vaccines.